Local injections of β-NGF accelerates endochondral fracture repair by promoting cartilage to bone conversion - Rivera, Kevin O.; Russo, Fabrizio; Boileau, Ryan M.; Tomlinson, Ryan E.; Miclau, Theodore; Marcucio, Ralph S.; Desai, Tejal A.; Bahney, Chelsea S. (Scientific reports, 2020)
There are currently no pharmacological approaches in fracture healing designed to therapeutically stimulate endochondral ossification. In this study, we test nerve growth factor (NGF) as an understudied therapeutic for fracture repair. We first characterized endogenous expression of Ngf and its receptor tropomyosin receptor kinase A (TrkA) during tibial fracture repair, finding that they peak during the cartilaginous phase. We then tested two injection regimens and found that local β-NGF injections during the endochondral/cartilaginous phase promoted osteogenic marker expression. Gene expression data from β-NGF stimulated cartilage callus explants show a promotion in markers associated with endochondral ossification such as Ihh , Alpl , and Sdf-1 . Gene ontology enrichment analysis revealed the promotion of genes associated with Wnt activation, PDGF- and integrin-binding. Subsequent histological analysis confirmed Wnt activation following local β-NGF injections. Finally, we demonstrate functional improvements to bone healing following local β-NGF injections which resulted in a decrease in cartilage and increase of bone volume. Moreover, the newly formed bone contained higher trabecular number, connective density, and bone mineral density. Collectively, we demonstrate β-NGF’s ability to promote endochondral repair in a murine model and uncover mechanisms that will serve to further understand the molecular switches that occur during cartilage to bone transformation.